2021
DOI: 10.1177/10398562211009247
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between psychosocial trauma type and conversion (functional neurological) disorder symptoms: a cross-sectional study

Abstract: Objective: Psychosocial trauma was associated with developing conversion disorder (also known as functional neurological disorder) before Freud, though why a particular symptom should arise is unknown. We aimed to determine if there was a relationship between trauma type and symptom. Methods: We retrospectively reviewed the medical records of patients attending Australia’s first functional neurology clinic, including referral, clinic letters and a clinic questionnaire. Results: There were 106 females, 43 males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
(14 reference statements)
2
6
0
Order By: Relevance
“…Medical records on all transgender people seen in a public FND clinic in Melbourne (Morsy et al., 2021) were obtained and compared with the clinic’s other patients. Comparisons were made using chi-square tests, unless indicated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Medical records on all transgender people seen in a public FND clinic in Melbourne (Morsy et al., 2021) were obtained and compared with the clinic’s other patients. Comparisons were made using chi-square tests, unless indicated.…”
Section: Methodsmentioning
confidence: 99%
“…There is a marked difference between the genders in the prevalence of functional neurological disorder (FND). Though no longer considered an exclusively female malady, women are at least twice as likely to develop FND (Morsy et al., 2021). The reasons behind this are unknown, with biological, cultural and social explanations suggested (Chouksey and Pandey, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One cross-sectional study of an Australian adult FND clinic found a higher proportion of TGNC patients than would be expected based on census data, although the authors speculated that there may have been an underrepresentation of TGNC individuals in the census. 38 A case report from Israel described an adolescent who presented with dense hemiparesis, hemisensory loss, and unilateral diminished reflexes that mimicked an acute stroke. 39 These symptoms occurred during a period of “severe emotional stress while questioning his gender identity.” Orfanelli and Borkowski detailed their care of a 10-year-old transgender boy with FND.…”
Section: Functional Neurologic Disorders In Tgnc Individualsmentioning
confidence: 99%
“…PTSD is the result of vulnerable genetics and less-than-optimal events of fate. i.e., biography informs and impacts the response of biology (Morsy et al, 2021). The comprehensive study of stress and trauma has origins in the field of physics, with the earliest research being conducted by stress research pioneer Hans Seyle (1965).…”
Section: Epigenetic Gene Expression Genetic Markers and Generational ...mentioning
confidence: 99%